CONTROL OF AIRCRAFT TRAJECTORIES IN THE CONDITIONS OF THE NAVIGATION SESSION OPTIMIZATION AT AUTOMATIC DEPENDENT SURVEILLANCE - V. V. Erokhin (Научный вестник МГТУ ГА)
Algorithms of determination of coordinates of the aircraft in the integrated system of navigation and optimum control of a trajectory are considered. Results of researches of parameters of a navigation session and precision characteristics of an assessment of location showed that application of optimum control of a trajectory allowув to increase the accuracy of navigation definitions in case of incomplete constellation of navigation satellites.